History and Development of the Accused’s Right to Testify - Robert Popper (Washington University Law Quarterly, 1962)
Issues dealing with the individual’s right to remain silent despite interrogation and accusation by governmental authorities have raised topical and provocative questions and discussions in this country over the last decade. However, the subject can be best appreciated when it is realized that its roots are entwined in the history of the common law and that its present structure is but a stage in a development spanning the centuries.
Keywords: Criminal procedure